2017
DOI: 10.1016/j.cropro.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Spray droplet impaction outcomes for different plant species and spray formulations

Abstract: A track-sprayer combined with a high-speed camera were used to visualize and identify droplet impaction outcomes for three formulations (water, 0.1% LI 700® (lecithin, a mixture of soya oils, propionic acid and surfactants) in water and 0.1% Pulse® (non-ionic surfactant, trisiloxane ethoxylate) in water) on four plant species (bean (Vicia faba L.), avocado (Persea americana L.), barnyard grass (Echinochloa crus-galli L. P. Beauv.) and cabbage (Brassica oleracea L.)) selected to represent a wide range of leaf s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(72 citation statements)
references
References 42 publications
1
71
0
Order By: Relevance
“…The PRSm software outputs showed (Fig. ) that the position a spray drop impacts the leaf can affect the outcome, reflecting the experimental results . As shown in Fig.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The PRSm software outputs showed (Fig. ) that the position a spray drop impacts the leaf can affect the outcome, reflecting the experimental results . As shown in Fig.…”
Section: Resultssupporting
confidence: 60%
“…The impaction of a drop onto a leaf surface can result in adhesion, bounce or shatter, the outcome being dependent on formulation, leaf surface character, droplet size and velocity . Furthermore, Massinon et al . demonstrated that more than one of these impaction outcomes can occur under the same conditions when impacting the same leaf surface.…”
Section: Introductionmentioning
confidence: 99%
“…To characterize the uniformity of droplet deposition between spray width, the uniformity of droplet deposition was measured by the coefficient of variance (CV) of droplet deposition densities at different locations of the processing pepper plants within the UAV sprayer's effective spray width. The CV of the droplet deposition density was calculated by Equations 1and (2) [16,23]:…”
Section: Treatmentmentioning
confidence: 99%
“…There are very many experimental studies of droplets impacting on synthetic surfaces, [6][7][8][9][10][11] but there are far fewer studies of droplets impacting on leaf surfaces over very short time scales. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] This study contributes to this research by reporting on droplet impaction experiments on leaves from two plant species, one artificial surface, and three aqueous formulations.…”
Section: Introductionmentioning
confidence: 95%
“…7,8,10,11 The surface properties of a leaf also play a major role, because its roughness and chemistry affect the affinity between the formulation and the leaf surface. 12,[15][16][17][18][19]24 An impact can result in three broad outcomes: (i) adhesion, when the totality of the drop sticks to the surface; (ii) bouncing, when the drop rebounds as a single object; and (iii) shatter, when multiple secondary droplets are ejected radially. The impact outcome reflects the balance between inertia, viscosity, capillary and cohesive forces.…”
Section: Introductionmentioning
confidence: 99%